If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 5y + 1 = 0 Reorder the terms: 1 + 7x + 5y = 0 Solving 1 + 7x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + 7x + -1 + 5y = 0 + -1 Reorder the terms: 1 + -1 + 7x + 5y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 7x + 5y = 0 + -1 7x + 5y = 0 + -1 Combine like terms: 0 + -1 = -1 7x + 5y = -1 Add '-5y' to each side of the equation. 7x + 5y + -5y = -1 + -5y Combine like terms: 5y + -5y = 0 7x + 0 = -1 + -5y 7x = -1 + -5y Divide each side by '7'. x = -0.1428571429 + -0.7142857143y Simplifying x = -0.1428571429 + -0.7142857143y
| -2(m-13)+-5=-9 | | 5*8(2*9)/4 | | -(8x+12)=(3x-(-13)) | | 3q-15=9+5q | | (X/7)=-4 | | f(-20)=0.25x+260 | | 12w-10w-2=14 | | Y=(1/2)^2-1/2-42 | | 5*sin(x)=3-cos(2x) | | -16u+11u+10=-20 | | 1.8n=0.5n-11.44 | | 3x+6=-111-10 | | -6.6r=-4.7r+13.3 | | 3.1(f-14)+6.7=12.9 | | 5y+12=92 | | 9x+3=(-9x-10) | | -12.3b-12.95-9.94=-7.71-11.2b | | 4(5x-7)=10x+3 | | -2.6h+10.9=-4.4h-14.84 | | (3-x)=4 | | -14.87-4.5f=-3f+13.93 | | 3x+[4(x-1)]=45 | | -5.8f-13.89=-4.3f+12.96 | | y=4a+4a | | 14h+10=11h-8h-12 | | 2-13y=-13-14y | | 13h-12h+1=20 | | 12n+24=60 | | k^2+15k-25=0 | | 19j+18=18j | | 2n-n=7 | | -p-9=7p-1 |